2018
DOI: 10.9745/ghsp-d-16-00290
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of SMS Technology on Timely Community Health Worker Follow-Up for Childhood Malnutrition: A Retrospective Cohort Study in sub-Saharan Africa

Abstract: In Ghana, Rwanda, Senegal, and Uganda, we found positive association between community health workers (CHWs) using SMS data entry with reminder alerts and timely follow-up for childhood malnutrition screening visits compared with paper forms. This association was strongest when CHWs used SMS data entry consecutively over multiple visits than when they switched between SMS and paper forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… The Global Initiative on Health Technologies (Howitt et al, 2012)  AI-powered Chabots in China (Guo & Li, 2018)  ICT-enabled mobile application to assist healthcare delivery for infants and young children under 5 years in Nigeria (Eze et al, 2019)  Low-cost telecommunication systems for rural primary healthcare personnel such as 'Hispano-American Health Link' (Martínez et al, 2004)  Pan Africa Project providing Tele-consultation services in Egypt and India (Combi et al, 2016)  Malnutrition screening in under 5-years children in Ghana (Sarma et al, 2018)  Mobile Alliance for Maternal Action in South Africa (Coleman et al, 2020)  The e-NABLING future project providing 3D printing of prosthetics (Elmansy, 2015)  SIMpill for improvement of treatment adherence among TB patients in Cape town (Barclay, 2009  Public-private partnership led by Pfizer Global Health Fellows programme (Vian et al, 2007)  Carabayllo project in Peru (Berwick, 2004)  The Millennium Villages Project: a multisectoral, rural development project (Mitchell et al, 2018)  The South-South Initiative in tropical diseases research (Holt et al, 2012)  Collaboration of four sub-Saharan countries to design and run a joint Master Programme with a focus on health workforce (Amde et al, 2014)  Capacity building among hospital managers of Iran in collaboration with World Health Organization (Doshmangir & Takian, 2019)  The Observatory of Human Resources in Health Sector Reforms for the Americas (World Health Organization, 2003a)  The project from the Italian association Patologi Oltre Frontiera for cancer prevention in Zambia (Combi et al, 2016)…”
Section: Riding the Wave Of Emerging Technologies And Seizing The Win...mentioning
confidence: 99%
“… The Global Initiative on Health Technologies (Howitt et al, 2012)  AI-powered Chabots in China (Guo & Li, 2018)  ICT-enabled mobile application to assist healthcare delivery for infants and young children under 5 years in Nigeria (Eze et al, 2019)  Low-cost telecommunication systems for rural primary healthcare personnel such as 'Hispano-American Health Link' (Martínez et al, 2004)  Pan Africa Project providing Tele-consultation services in Egypt and India (Combi et al, 2016)  Malnutrition screening in under 5-years children in Ghana (Sarma et al, 2018)  Mobile Alliance for Maternal Action in South Africa (Coleman et al, 2020)  The e-NABLING future project providing 3D printing of prosthetics (Elmansy, 2015)  SIMpill for improvement of treatment adherence among TB patients in Cape town (Barclay, 2009  Public-private partnership led by Pfizer Global Health Fellows programme (Vian et al, 2007)  Carabayllo project in Peru (Berwick, 2004)  The Millennium Villages Project: a multisectoral, rural development project (Mitchell et al, 2018)  The South-South Initiative in tropical diseases research (Holt et al, 2012)  Collaboration of four sub-Saharan countries to design and run a joint Master Programme with a focus on health workforce (Amde et al, 2014)  Capacity building among hospital managers of Iran in collaboration with World Health Organization (Doshmangir & Takian, 2019)  The Observatory of Human Resources in Health Sector Reforms for the Americas (World Health Organization, 2003a)  The project from the Italian association Patologi Oltre Frontiera for cancer prevention in Zambia (Combi et al, 2016)…”
Section: Riding the Wave Of Emerging Technologies And Seizing The Win...mentioning
confidence: 99%
“…Earlier research has shown that they have high response rates, are user-friendly [8] and inexpensive [9]. The method opens the door for gathering information from populations that may otherwise be difficult to reach, for example rural communities [10], low resource settings [11] but possibly also those with limited computer access or highly mobile individuals. Moreover, the method reduces data handling errors as the responses are registered in the data file directly [9].…”
Section: Introductionmentioning
confidence: 99%